Identification the Potential Types of Fungi on Establishment Agarwood Stem of Aquilaria spp. - Sri Wilarso Budi R.; Erdy Santoso; Akhmad Wahyudi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2010)
One of tree genus that becomes the main source of agarwood producer is Aquilaria. The formation of agarwood was believed as response of agarwood trees to many factors, likes plant physiological and pathogenic fungi infection. A number of isolates that have the potential to induce agarwood has been isolated from wood samples from different areas such as Bangka, Bogor, Bohorok, Gorontalo, East Kalimantan, Lampung, Mentawai, Papua, and Sukabumi. This study aimed to obtain information on the types of fungi isolated from stem-forming agarwood Aquilaria spp that successful collection of Microbiology Laboratory of Forestry Research in Bogor. Identification was done by observing morphological features from cultured isolates on PDA and BLA. The results of identification of isolates collection include species of Fusarium solani (Mart.), Appell and Walenw, F. tricinctum (corda) Sacc, F sambucinum Fuckel, and F. Moniliformae.